The Relationship Between Transformational Leadership Behaviors and Organizational Citizenship Behavior - Siti Salasiah, Wan (2009)
The main objective of this study is to determine the relationship between transformational leadership behavior and its dimensions and organizational citizenship behavior (OCB). The dimensions of transformational leadership behavior are idealized influence, inspirational motivation, intellectual stimulation and individualized consideration. This study also intends to examine whether any differences on OCB exist among the respondents based on the length of time they have been in their current grade and their place of work. Respondents of this study were 190 senior officers of grade 41 and 44 of Royal Malaysian Customs Department at Pulau Pinang, Wilayah Persekutuan Kuala Lumpur,Pahang, Johor, and Kuala Lumpur International Airport. Data were analyzed using SPSS version 15. The tests conducted were Pearson’s Correlation,multiple regression and one-way ANOVA. The Pearson’s Correlation showed that transformational leadership behavior, as well as each of its dimensions was correlated to OCB. However, multiple regression tests showed that OCB was significantly influenced by only one dimension; idealized influence. The findings of the one-way ANOVA showed that there were significant differences in respondents OCB based on the length of time they have been in their current grade. It was also found that there were no differences in respondents’ OCB based on their place of work.